2005
DOI: 10.1002/uog.1892
|View full text |Cite
|
Sign up to set email alerts
|

The role of ultrasound imaging in diagnosing and investigating early pregnancy failure

Abstract: The advent of high-resolution transvaginal ultrasound (TVS) has revolutionized our understanding of the pathophysiology and the management of early pregnancy failure. Knowledge of the ultrasound appearances of normal early pregnancy development and a good understanding of its pitfalls are essential for the diagnosis and management of early pregnancy failure. Ultrasound imaging has rapidly replaced all other techniques used to study normal human development in the first trimester, and ultrasound features of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
97
1
23

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(125 citation statements)
references
References 120 publications
(148 reference statements)
4
97
1
23
Order By: Relevance
“…One study demonstrated, that, the rate of miscarriage after visualization of foetal heart is higher in women with threatened miscarriage, when compared with a control group without bleeding (5.5 versus 1.9%). 2 In our study, we did not find that women were more likely to have an early miscarriage if they presented with bleeding, once the foetal heart was visualized in early pregnancy.…”
Section: Discussioncontrasting
confidence: 65%
“…One study demonstrated, that, the rate of miscarriage after visualization of foetal heart is higher in women with threatened miscarriage, when compared with a control group without bleeding (5.5 versus 1.9%). 2 In our study, we did not find that women were more likely to have an early miscarriage if they presented with bleeding, once the foetal heart was visualized in early pregnancy.…”
Section: Discussioncontrasting
confidence: 65%
“…The associations between a low fetal heart rate, yolk sac size, and chromosomal abnormalities have been investigated in previous studies [31][32][33]. We did not examine these factors in detail in this study because they overlap with (or are included in) the six categories of ultrasound findings examined here.…”
Section: Association Between Ultrasound Findings and Chromosomal Abnomentioning
confidence: 99%
“…Pregnancy failure has been determined with sonography using multiple measurements including the mean gestational sac diameter, embryonic pole, and embryonic heart pulsations. The sonographic diagnostic cut-offs for pregnancy failure vary depending the degree specificity, sensitivity and the different author's findings; however, the more common guidelines are summarized in Table 1. 14, 16,[26][27][28] The gestational sac can first be observed by TVS when the sac diameter is 5 mm at approximately 5 weeks gestation (or 3 weeks postconception). Between the fifth and sixth weeks of pregnancy, the MSD increases by approximately l1 mm/day.…”
Section: Diagnosing Pregnancy Failurementioning
confidence: 99%
“…[50][51][52] It has been hypothesized that the higher resistance maternal like flow promotes oxidative stress and then further damage to the embryo which may contribute to pregnancy failure. 27 The abnormal placental resistance patterns documented by Doppler and associated with early pregnancy failure are not clinically useful in diagnosing miscarriage. However, the use of Doppler in the late first trimester may become a more useful tool in predicting other developing placental diseases like pre-eclampsia and molar pregnancies.…”
Section: First Trimester Doppler: the Corpus Luteum And Pregnancy Faimentioning
confidence: 99%